“Draw a Guerrilla!” Betrayal, Solitude, and Revolutionary Art - James Scorer (Latin American Research Review)
This article analyzes the sketches of Ernesto “Che” Guevara and fellow guerrillas made by the Argentine Ciro Bustos during his captivity in Bolivia in 1967. Many of the references to Bustos in biographies of Guevara and in writings about the latter’s failed Bolivian campaign depict Bustos, because of those sketches, as “the man who betrayed Che.” The tensions and discrepancies in those accounts suggest instead that Bustos’s sketches should be seen not merely as documents of betrayal but as artworks embedded in the period’s wider revolutionary visualities. The article argues that Bustos’s drawing of Che Guevara, who is usually depicted visually as “heroic guerrilla” or “saintly martyr,” introduces an affective, intimate gaze of armed struggle in all its complications.